(untitled) (Constructionism Conference Proceedings, 2025)
This study examines “creative deviation” as a new assessment method to promote learners’ interests, engagement, and creativity within STEAM education. Mock lessons centered on food were conducted, during which deviations from standard classroom progression were carefully observed. These behaviors were evaluated using originality criteria from contemporary art. The study hypothesizes that creative deviations can initiate creativity that drives innovation in a diverse society. This research explores the application and potential of creative deviation as an effective tool for assessing and fostering student creativity.